HR's Role in Developing Incentive Programs for Micro Influencers in Social Media Marketing - Mansyur, Nadhila Adelfrini (Celebes Scholar pg, 2024)
The purpose of this research is to analyse the dynamic position of Human Resources (HR) in designing and implementing incentives for micro influencers in the fashion, technology, and the Fast Moving Consumer Goods (FMCG) sector. Drawing on a phenomenological research paradigm, the study aims at understanding how HR departments of companies associated with digital marketing are responding to the fluctuating demands of the field and, therefore, designing original and versatile incentive systems that appeal to the micro influencers self-motivational factors. The studies show that simple incentive structures and mainly monetary based incentives are incapable of encouraging sustained participation. However, using organization specific professional development opportunities, brand management, and public recognition is crucial. In the same respect, the study also reveals how the role of HR is important in influencer marketing where it involves working closely with the marketing department to ensure that influencer practices are in line with the rest of the organization. Additionally, the implications of the research cover the issues related to the formalization of the influencer relationships, which may indeed be challenging when gaining the necessary degree of control for the proper management of the influencer’s work, while at the same time remaining consistent with the creative freedom which is required for the influencer content. Hence, this study adds to the existing literature on the subject of HR for the digital economy as it provides best practice guidelines for HR managers that can help organizations to navigate through the ethical and cultural aspects of influencer collaboration.